Acute whole body vibration is associated with spinal and supraspinal adaptations - Krause, A.; Freyler, K.; Gollhofer, A.; Ritzmann, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Whole body vibration (WBV) has been demonstrated to improve functional movement control (Rittweger, 2010), but the knowledge about the underlying neurophysiological mechanisms remains fragmentary: Investigations have shown an inhibition of spinal excitability shortly after WBV while corticospinal modulation has been reported to be facilitated - but during WBV, only. Especially evidence regarding the maintenance of adaptations following vibration has not been clarified, yet. Therefore, this study aimed to investigate the acute adaptations of corticospinal and spinal excitability to WBV in one study. Methods: In 44 healthy subjects corticospinal (A) and spinal adaptations (B) were tested before (t1), immediately (t2), 2 (t3), 4 (t4) and 10min (t5) after a 1-min-bout of WBV (30Hz, 3mm). (A) Transcranial magnetic and (B) Peripheral nerve stimulation were applied respectively, with the changes in motor evoked potentials (MEP) and H-reflexes being assessed in the m. soleus (SOL) and the m. gastrocnemius medialis (GM) by an rmANOVA. Body position was controlled with background electromyography (EMG) of SOL, GM as well as m. tibialis anterior (TA) and goniometric recordings of ankle and knee joint excursions with equivalence statistics. Results: After vibration, (A) MEPs were significantly elevated in SOL compared to baseline values (t2 +15%, t3 +22%, t4 +15%, t5 +20%; P<0.05), but did not change significantly in GM (t2 +32%, t3 +9%, t4 +8%, t5 +22%; P=0.07). In contrast, (B) H-reflexes were diminished for SOL (t2 -19%, t3 -21%, t4 -20%, t5 -14%; P<0.05) as well as GM (t2 -14%, t3 -16%, t4 - 18%, t5 -16%; P<0.05). Statistical equivalence was observed for SOL background EMG, ankle and knee joint deflections for (A) as well as SOL and GM background EMG and ankle joint deflections for (B). Discussion: After an acute bout of WBV, results revealed (A) a sustaining facilitation of corticospinal pathways concomitant with (B) a suppression in spinal circuits. Those effects persisted for a minimum of 10 minutes and might illustrate increased corticospinal excitability while spinal excitability is inhibited. Functionally, those adaptations may point towards increased voluntary motor control (Chen and Zhou, 2011; Nielsen and Petersen, 1995): Facilitation comprising the origin of supaspinal structures might be associated with greater central movement control. Especially for populations with neurological motor diseases affecting the locomotor system this finding might be beneficial regarding motor learning and voluntary movement execution.